Attitude towards patients with epilepsy - Yakovenko Анна; Kleban Катерина (Psychosomatic Medicine and General Practice, 2019)
This is a conference abstract from the "Psychosomatic Medicine Of The XXI Century: Realities And Perspectives" Congress. It is dedicated to the attitude towards patients with epilepsy.